Assessment on Application Effect of Intelligent Pressure Ulcer Information Management System Software - Guo, Lanping; Lu, Jing; Yang, Xuan; Gong, Lina (Iranian journal of public health, 2023)
Background: We aimed to apply the intelligent pressure ulcer information management system software to hospitalized patients with pressure ulcer and to evaluate its application effect. Method: Fifty patients hospitalized in the Third Xiangya Hospital of Central South University, Changsha, China, a grade-A tertiary hospital from March 2021 to May 2021 were grouped into the control group. For these subjects, conventional electronic forms were used to report and manage pressure ulcer information. Another 50 patients with pressure ulcer were selected as the experimental group who were hospitalized the same hospital from June 2021 to August 2021.They were managed with Intelligent Pressure Ulcer Information Management System Software. Results: The effects of the two management methods were assessed by comparing the reporting time, the degree of pressure ulcer healing 1 week after the occurrence of pressure ulcer and after discharge, and the nurse satisfaction. The reporting time and Design-R scores 1 week after the occurrence of pressure ulcer and after discharge were significantly lower than those of the control group (P<0.05). Conclusion: The pressure ulcer information management system makes the reporting process simple and convenient, which saves the reporting time, improves the accuracy of the pressure ulcer staging. It achieved the guidance for various stages of pressure ulcer treatment program, the use of dressing guidance, improved the accuracy of pressure ulcer treatment program, which is worthy of clinical reference.